EVALUASI BLOK TEGANGAN TEKAN EKUIVALEN BALOK BETON BERTULANG AGREGAT LIMBAH BATU ONYX TULUNG AGUNG - R., Bobby Asukmajaya; Wahjuni S., Edhi; Wisnumurti, Wisnumurti (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2021)
Normal aggregate replacement to the onyx waste aggregate will certainly make the compressive strength and modulus of elasticity different, so it will affect the value of the compressive stress block equivalent (Î²1) as a result of the extent of the changing stress strain curve. In this study, trying to compare between the experimental Î²1 value of onyx concrete, while analytically the Î²1 value for normal concrete was obtained in accordance with SNI 2847 - 2019. To get the experimental Î²1 value from onyx concrete, it is made by looking for the compressive strength, elastic modulus and êœ«0, for later the stress strain curve of the concrete is made to find the experimental Î²1 value of the onyx concrete.The results were obtained if the average Î²1 value of 18 specimens of onyx coarse aggregate concrete with an average compressive strength of 32.92 MPa was 0.868 while the analytical Î²1 value based on SNI 2847-2019 was 0.839, This shows that theÂ Î²1Â value for concrete with other aggregates is different, so it needs to be checked experimentally.